Teknik Color Grading untuk Memperkuat Nuansa Horor pada Film Lights out - Nurul A’ini; Dani Manesah (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2025)
This study explores the application of color grading techniques to enhance the horror atmosphere in the film Lights out. In the horror genre, creating a tense atmosphere heavily relies on visual elements, including the use of color and lighting. By manipulating these elements, films can heighten the emotional intensity experienced by the audience. This research employs visual analysis and in-depth interviews with industry practitioners to identify specific color grading techniques used in Lights out. The findings reveal that a combination of certain color palettes, low lighting, and sharp contrasts play a crucial role in creating an effective eerie atmosphere.